PENGARUH EKSTRAK AIR DAN ETANOL Kaempferia spp. TERHADAPAKTIVITAS DAN KAPASITAS FAGOSITOSIS SELMAKROFAG YANG DIINDUKSI BAKTERI Staphylococcus epidermidis - Tri Murningsih (BERITA BIOLOGI, 2010)
Ethanol 95% and water extracts of Kaempferia spp. (K. galanga, K. angustifolia, K. pandurata and K. rotunda) were tested for their influences in in-vitro phagocytosis activity and phagocytosis capacity of mouse peritoneum macrophage cells induced by Staphylococcus epidermidis. Extracts were tested at a series concentration in logarithmic order (0.1-1000) ug/ml. Imboost and distilled water were employed as positive and negative controls, respectively. The results shows that almost all extracts were capable to increase on phagocytosis activity (SPA - Screening for Phagocytosis Activity) and phagocytosis capacity (IP • Index Phagocytosis) of macrophage cells compared to positive and negative controls significantly (p<0.05).The phagocytosis activity and capacity macrophage cells were increased by increasing extract concentration. K.rotunda extracts shows reveal better on above activities in low concentration (0.1-100) ug/ml then other species.